Homologs of bacterial heat-labile enterotoxin subunit A contribute to development, stress response, and virulence in filamentous entomopathogenic fungus Beauveria bassiana - Ding, Jin-Li; Wei, Kang; Feng, Ming-Guang; Ying, Sheng-Hua (Frontiers in Immunology, 2023)
Introduction Enterotoxigenic bacteria commonly excrete heat-labile enterotoxins (LT) as virulence factors that consist of one subunit A (LTA) and five B subunits (LTB). In fungi, there are a large number of genes encoding the homologs of LTA, but their biological roles remain largely unknown. Methods In this study, we identified 14 enterotoxin_A domain proteins in filamentous fungus B. bassiana in which five proteins were functionally characterized. Results Five proteins displayed diverse sub-cellular localizations but perform convergent functions in stress response, development, and virulence. The loss of five LTA genes resulted in significant reduction in conidial production, blastospore formation, and the increased sensitivity to oxidative and cell wall –perturbing stresses. The virulence of five disruptants was notably weakened as indicated by topical and intrahemocoel injection assays. Notably, the loss of these five proteins led to the significant changes in the carbohydrate profiles of cellular surface, which induced the enhanced host immune reactions of encapsulation and melanization. Discussion Thus, LTA proteins contribute to the fungus–host interaction via maintaining the carbohydrate profiles of cellular surface. This study expands our understanding of the enterotoxin_A domain proteins in fungal physiology and deepens mechanisms involved in the lifestyle of fungal insect pathogens.